A new direction for prenatal chromosome microarray testing: software-targeting for detection of clinically significant chromosome imbalance without equivocal findings - Ahn,Joo Wook; Bint,Susan; Irving,Melita D; Kyle,Phillipa M; Akolekar,Ranjit; Mohammed,Shehla N; Mackie Ogilvie,Caroline (PeerJ PrePrints, 2014)
Purpose. To design and validate a prenatal chromosome microarray testing strategy that moves away from size-based detection thresholds, towards a more clinically relevant analysis, providing higher resolution than G-banded chromosomes but avoiding the detection of imbalances of unclear prognosis that cause parental anxiety. Methods. All prenatal samples fulfilling our criteria for karyotype analysis (n=342) were tested by chromosome microarray and only copy number variants of established deletion/duplication syndrome regions and any other imbalance >3Mb were detected and reported. A retrospective full-resolution analysis of 249 of these samples was carried out to ascertain the performance of this testing strategy. Results. Using our prenatal analysis, 23/342 (6.7%) samples were found to be abnormal. Of the remaining samples, 249 were anonymized and reanalyzed at full-resolution; a further 46 regions of imbalance were detected in 44 of these traces (17.7%). None of these additional imbalances were of clear clinical significance. Conclusion. This prenatal chromosome microarray strategy detected all CNVs of clear prognostic value and did not miss any imbalances of clear clinical significance. This strategy avoided both the problems associated with interpreting imbalances of uncertain prognosis and the parental anxiety that are a result of such findings.
Keywords: array CGH; CMA; software targeting; prenatal; VUS; prenatal testing